SILICON DIOXIDE BASED OXIDE GLASS FOR VIAL GLASS BOTTLE HAVING HARDNESS OF 800Hv OR MORE AND HIGH HARDNESS AND METHOD OF MANUFACTURING THEREOF
A silicon dioxide-based glass composition with controlled components addresses the limitations of conventional vial glass bottles by achieving high hardness and low thermal expansion, ensuring robust thermal stability and shock resistance for pharmaceutical packaging.
Patent Information
- Application Number
- KR1020250054230
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-04-25
AI Technical Summary
Conventional vial glass bottles made from borosilicate and alkali aluminosilicate oxide glasses face issues with formability, high melting temperatures, volatilization, and difficult molding conditions, limiting their suitability for pharmaceutical packaging.
A silicon dioxide-based oxide glass composition with controlled components and ratios, including Na2O, K2O, MgO, CaO, Al2O3, SiO2, ZrO2, B2O3, and P2O5, is formulated and processed to achieve a hardness of 800 Hv or more and a low coefficient of thermal expansion of 800 × 10^-6 /℃ or less, ensuring excellent thermal stability and resistance to external shock.
The silicon dioxide-based glass achieves a high hardness and low thermal expansion, enabling vial glass bottles with enhanced thermal stability and shock resistance, suitable for pharmaceutical packaging.
Smart Images

Figure 112025047092328-PAT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more and a method for manufacturing the same, and more specifically, by strictly controlling each component of the glass composition and the ratio of its components, 7.5 × 10 -6 The present invention relates to a silicon dioxide-based oxide glass for a vial with a hardness of 800 Hv or more, and a method for manufacturing the same, which has a low coefficient of thermal expansion of 800 Hv or less and a high hardness of 800 Hv or more, thereby making it possible to manufacture a vial with excellent thermal stability and resistance to external impact when used as a vial glass bottle. Background Technology
[0003] Generally, glass has been used as the preferred material for packaging pharmaceuticals due to its airtightness, optical transparency, and excellent chemical durability compared to other materials. Specifically, the glass used for pharmaceutical packaging must possess adequate chemical durability so as not to affect the stability of the pharmaceutical composition contained therein.
[0004] In particular, among medicine bottles, there is a slim type of glass bottle commonly called a vial, which is mainly used to increase convenience in storage and transport by individually packaging biopharmaceuticals such as injectable solutions or oral medications in single doses.
[0005] Conventionally, vial glass bottles were mainly manufactured using borosilicate oxide glass or alkali aluminosilicate oxide glass.
[0006] However, borosilicate oxide glass had a problem with very poor formability due to its relatively high melting temperature, the volatilization of boron oxide, and slow curing speed. In addition, alkali aluminosilicate oxide glass had a problem with very difficult molding conditions due to its high melting temperature and very fast curing speed.
[0007] Accordingly, research is currently underway to utilize silicon dioxide-based oxide glass as vial bottles.
[0008] A relevant prior art document is Korean Patent Publication No. 10-2023-0107437 (published July 17, 2023), which describes a glass composition, a glass product manufactured therefrom, and a display device. The problem to be solved
[0010] The objective of the present invention is to strictly control each component of the glass composition and the ratio thereof, thereby 7.5 × 10 -6 The present invention provides a silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more, and a method for manufacturing the same, which has a low coefficient of thermal expansion of 800 Hv or less and a high hardness of 800 Hv or more, thereby making it possible to manufacture a vial glass bottle that has excellent thermal stability and is resistant to external shock when used as a vial glass bottle. means of solving the problem
[0012] A silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to an embodiment of the present invention for achieving the above objective is characterized by comprising Na2O 10 to 20 mol%; K2O 0.1 to 1.5 mol%; MgO 0.5 to 2.0 mol%; CaO 0.5 to 2.5 mol%; Al2O3 12 to 16 mol%; SiO2 67 to 69.5 mol%; ZrO2 1 to 5 mol%; and 1 to 3 mol% of the sum of one or more of B2O3 and P2O5.
[0013] It is more preferable that the above Na2O is added in an amount of 12.5 to 13.5 mol% and the above K2O is added in an amount of 0.4 to 0.8 mol%.
[0014] It is most preferable to add the above Na2O and K2O in a combined amount of 13 to 14 mol%.
[0015] In addition, it is more preferable to add the above MgO and CaO in a combined amount of 1.5 to 2.5 mol%.
[0016] It is most preferable to add the above SiO2 and Al2O3 combined in an amount of 80 to 82 mol%.
[0017] In addition, it is more preferable that the above ZrO2 be added in an amount of 1.5 to 2.5 mol%.
[0018] It is most desirable to add at least one of the above B2O3 and P2O5 in a combined amount of 1.5 to 2.5 mol%.
[0019] The above silicon dioxide-based glass is 7.5 × 10 -6 It has a coefficient of thermal expansion of / ℃ or less and a hardness of 800 Hv or more.
[0020] The above silicon dioxide-based glass is 6 × 10 -6 / ℃ to 7.5 × 10 -6 It is more desirable to have a coefficient of thermal expansion of / ℃ and a hardness of 800 to 900 Hv.
[0022] A method for manufacturing silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to an embodiment of the present invention for achieving the above objective comprises: (a) a step of forming a silicon dioxide-based glass composition by mixing and stirring in a mixing ratio of 10 to 20 mol% Na2O, 0.1 to 1.5 mol% K2O, 0.5 to 2.0 mol% MgO, 0.5 to 2.5 mol% CaO, 12 to 16 mol% Al2O3, 67 to 69.5 mol% SiO2, 1 to 5 mol% ZrO2, and 1 to 3 mol% of the sum of one or more of B2O3 and P2O5; (b) a step of melting the silicon dioxide-based glass composition; and (c) a step of forming a silicon dioxide-based oxide glass by annealing the molten silicon dioxide-based glass composition and then cooling it.
[0023] In step (a) above, it is more preferable that the Na2O is added in an amount of 12.5 to 13.5 mol% and the K2O is added in an amount of 0.4 to 0.8 mol%.
[0024] It is most preferable to add the above Na2O and K2O in a combined amount of 13 to 14 mol%.
[0025] In step (a) above, it is more preferable to add the MgO and CaO in a combined amount of 1.5 to 2.5 mol%.
[0026] In step (a) above, it is most preferable to add the combined SiO2 and Al2O3 in an amount of 80 to 82 mol%.
[0027] In step (a) above, it is more preferable that the ZrO2 be added in an amount of 1.5 to 2.5 mol%.
[0028] In step (a) above, it is most preferable to add at least one of the above B2O3 and P2O5 in a combined amount of 1.5 to 2.5 mol%.
[0029] In step (b) above, the melting is carried out at 1,400 to 1,800°C for 1 to 6 hours.
[0030] In step (c) above, the annealing is performed at 300 to 800°C for 30 to 360 minutes.
[0031] After step (c) above, the silicon dioxide-based glass is 7.5 × 10 -6 It has a coefficient of thermal expansion of / ℃ or less and a hardness of 800 Hv or more.
[0032] The above silicon dioxide-based glass is 6 × 10 -6 / ℃ to 7.5 × 10 -6 It is more desirable to have a coefficient of thermal expansion of / ℃ and a hardness of 800 to 900 Hv. Effects of the invention
[0034] The silicon dioxide-based oxide glass for vials having a hardness of 800 Hv or more according to the present invention and the method for manufacturing the same produced silicon dioxide-based oxide glass having a high hardness of 800 Hv or more while having a low coefficient of thermal expansion by strictly controlling each component of the glass composition and the ratio of the components thereof.
[0035] Thus, the silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to the present invention and the method for manufacturing the same, by strictly controlling each component of the glass composition and the ratio of the components thereof, 7.5 × 10 -6 By having a low coefficient of thermal expansion of 1 / ℃ or less and a high hardness of 800 Hv or more, it is possible to manufacture a vial glass bottle that has excellent thermal stability and is resistant to external shock when used as a vial glass bottle.
[0036] As a result, the silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to the present invention and the method for manufacturing the same are 7.5 × 10 -6 When silicon dioxide-based oxide glass that simultaneously satisfies a low coefficient of thermal expansion of 1 / ℃ or less and a high hardness of 800 Hv or more is used as a vial, the thermal stability of the vial can be secured, and the vial can be reliably protected from external shocks. Brief explanation of the drawing
[0038] FIG. 1 is a process flowchart illustrating a method for manufacturing silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to an embodiment of the present invention. FIG. 2 is a graph showing the measurement results of the coefficient of thermal expansion of silicon dioxide-based oxide glass prepared according to Examples 1 and 2. Figure 3 is a graph showing the Vickers hardness measurement results of silicon dioxide-based oxide glass prepared according to Comparative Examples 1 and 2. Specific details for implementing the invention
[0039] The advantages and features of the present invention and the methods for achieving them will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the present invention is not limited to the embodiments disclosed below but may be implemented in various different forms. These embodiments are provided merely to ensure that the disclosure of the present invention is complete and to fully inform those skilled in the art of the scope of the invention, and the present invention is defined only by the scope of the claims. Throughout the specification, the same reference numerals refer to the same components.
[0040] The silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more and the method for manufacturing the same according to a preferred embodiment of the present invention will be described in detail below with reference to the attached drawings.
[0042] According to an embodiment of the present invention, silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more was manufactured by strictly controlling each component of the glass composition and the ratio of the components thereof, thereby producing silicon dioxide-based oxide glass having a low coefficient of thermal expansion and a high hardness of 800 Hv or more.
[0043] Thus, the silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to an embodiment of the present invention, by strictly controlling each component of the glass composition and the ratio thereof, has 7.5 × 10 -6 By having a low coefficient of thermal expansion of 1 / ℃ or less and a high hardness of 800 Hv or more, it is possible to manufacture a vial glass bottle that has excellent thermal stability and is resistant to external shock when used as a vial glass bottle.
[0044] As a result, the silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention is 7.5 × 10 -6When silicon dioxide-based oxide glass that simultaneously satisfies a low coefficient of thermal expansion of 1 / ℃ or less and a high hardness of 800 Hv or more is used as a vial, the thermal stability of the vial can be secured, and the vial can be reliably protected from external shocks.
[0046] To this end, the silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to an embodiment of the present invention comprises Na2O 10 to 20 mol%; K2O 0.1 to 1.5 mol%; MgO 0.5 to 2.0 mol%; CaO 0.5 to 2.5 mol%; Al2O3 12 to 16 mol%; SiO2 67 to 69.5 mol%; ZrO2 1 to 5 mol%; and 1 to 3 mol% of the sum of one or more of B2O3 and P2O5.
[0047] Here, it is more preferable that Na2O be added in an amount of 12.5 to 13.5 mol% and K2O be added in an amount of 0.4 to 0.8 mol%.
[0048] In addition, it is most desirable to add Na2O and K2O in a combined amount of 13 to 14 mol%.
[0049] In addition, it is more preferable to add 1.5 to 2.5 mol% of MgO and CaO combined.
[0050] In addition, it is more preferable to add 80 to 82 mol% of the sum of SiO2 and Al2O3.
[0051] In addition, it is more preferable to add ZrO2 in an amount of 1.5 to 2.5 mol%.
[0052] In addition, it is most desirable to add at least one of B2O3 and P2O5 in a combined amount of 1.5 to 2.5 mol%.
[0053] The silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention is 7.5 × 10 -6It has a coefficient of thermal expansion of / ℃ or less and a hardness of 800 Hv or more, more specifically, 6 × 10 -6 / ℃ to 7.5 × 10 -6 It has a coefficient of thermal expansion of / ℃ and a hardness of 800 to 900 Hv.
[0055] Below, the role and content of each component of the silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention will be explained in detail.
[0057] Na2O is an alkali oxide that is an essential component for lowering the glass transition temperature and softening point by generating non-crosslinked oxygen within the glass composition. Among alkali oxides, Na2O is most widely used in silicon dioxide-based oxide glasses for vials.
[0058] It is preferable that Na2O be added in an amount of 10 to 20 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 12.5 to 13.5 mol%. If Na2O is added in an amount of less than 10 mol%, the amount added is negligible, so it may be difficult to lower the glass transition temperature and the softening point. Conversely, if the molar ratio of Na2O is excessively added to exceed 20 mol%, it may cause problems such as increasing the coefficient of thermal expansion, so it is not desirable.
[0060] Like Na2O, K2O is an essential alkali oxide for lowering the glass transition temperature and softening temperature. Because K2O has a lower electric field strength than Na2O, it is an oxide capable of producing more non-crosslinked oxygen.
[0061] Accordingly, it is preferable that K2O be added in an amount of 0.1 to 1.5 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 0.4 to 0.8 mol%. If K2O is added in an amount less than 0.1 mol%, the amount added is negligible, making it difficult to lower the glass transition temperature and softening point. Conversely, if the molar ratio of K2O exceeds 1.5 mol% and is added in excess, it may cause problems such as increasing the coefficient of thermal expansion, so this is not desirable.
[0062] The two components of Na2O and K2O mentioned above act as representative network modifiers, and since excessive addition weakens the structure of the glass, it is most desirable to add the two components of Na2O and K2O in a combined total of 13 to 14 mol%.
[0064] MgO is an alkaline earth oxide and, like alkali oxides such as Na2O and K2O, is a component capable of lowering the glass transition temperature and softening temperature. However, in the silicon dioxide-based oxide glass according to the present invention, since it is a component that can strengthen the glass structure and make it compact only when added in an appropriate amount, it is desirable to add only a very small amount to lower the glass transition temperature and softening temperature. Accordingly, it is preferable that MgO be added in an amount of 0.5 to 2.0 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 0.8 to 1.2 mol%.
[0066] Like MgO, CaO is an alkaline earth oxide that can lower the glass transition temperature and softening temperature; however, unlike MgO, it does not make the glass structure dense and compact but generates only non-crosslinked oxygen, so it is desirable to add it in a slightly higher amount compared to MgO.
[0067] Accordingly, it is preferable that CaO be added in an amount of 0.5 to 2.5 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 0.8 to 1.2 mol%. If MgO is added in an amount less than 0.5 mol%, the amount added is negligible, making it difficult to lower the glass transition temperature and softening point. Conversely, if the molar ratio of MgO is excessively added to exceed 2.5 mol%, it may cause problems that increase the coefficient of thermal expansion.
[0068] The two components of MgO and CaO mentioned above act as representative network modifiers, and since excessive addition weakens the structure of the glass, it is most desirable to add the two components of MgO and CaO in a combined amount of 1.5 to 2.5 mol%.
[0070] SiO2 acts as a network-forming agent in silicon dioxide-based oxide glass used for vials and is a key component that forms the framework of the glass structure. Additionally, SiO2 is a component capable of raising the glass transition temperature and softening temperature.
[0071] It is preferable that such SiO2 be added in an amount of 67 to 69.5 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 67 to 68 mol%. If SiO2 is added in an amount less than 67 mol%, there is a problem in that the structure of the glass is weakened and water resistance is reduced. Conversely, if SiO2 is added in an amount exceeding 69.5 mol%, it may cause a problem in that the coefficient of thermal expansion increases and the hardness decreases.
[0073] Al2O3, like SiO2, acts as a network-forming agent and is an oxide that makes the glass structure dense and compact when added to glass in amounts lower than that of Na2O.
[0074] Accordingly, it is preferable that Al2O3 be added in an amount of 12 to 16 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 12 to 14 mol%. If Al2O3 is added in an amount less than 12 mol%, it may be difficult to make the structure of the glass dense and compact. Conversely, if Al2O3 is added in an amount exceeding 16 mol%, it may cause problems such as increased coefficient of thermal expansion and reduced hardness.
[0075] The two components of SiO2 and Al2O3 act as network-forming agents within the glass and serve as key components forming the framework of the glass structure; it is most desirable to add the two components of SiO2 and Al2O3 in a combined total of 80 to 82 mol%.
[0077] ZrO2 is a component that can lower the coefficient of thermal expansion when added to a glass structure. However, adding too much ZrO2 makes the glass manufacturing process itself very difficult.
[0078] Accordingly, it is preferable that ZrO2 be added in an amount of 1 to 5 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and more preferable that it be added in an amount of 1.5 to 2.5 mol%.
[0080] B2O3 and P2O5 are both network-forming oxides that form a glass structure, and since their melting points are lower than those of SiO2, they are used to lower the softening point of the glass. In particular, when B2O3 and P2O5 are added to glass, the effect of increasing hardness is excellent. Therefore, it is preferable to add at least one of B2O3 and P2O5 in a combined amount of 1 to 3 mol% of the total molar ratio of the silicon dioxide-based oxide glass according to the present invention, and it is more preferable to add 1.5 to 2.5 mol%.
[0082] A method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention will be described below with reference to the attached drawings.
[0083] FIG. 1 is a process flowchart illustrating a method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention.
[0084] As illustrated in FIG. 1, a method for manufacturing silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more according to an embodiment of the present invention includes a mixing step (S110), a melting step (S120), and an annealing step (S130).
[0086] mix
[0087] In the mixing step (S110), a silicon dioxide-based glass composition is formed by mixing and stirring at a ratio of 10 to 20 mol% Na2O, 0.1 to 1.5 mol% K2O, 0.5 to 2.0 mol% MgO, 0.5 to 2.5 mol% CaO, 12 to 16 mol% Al2O3, 67 to 69.5 mol% SiO2, 1 to 5 mol% ZrO2, and 1 to 3 mol% of the sum of one or more of B2O3 and P2O5.
[0088] More specifically, when manufacturing a silicon dioxide-based glass composition, it is preferable to use raw materials with a purity of 99% or higher, and the raw materials used for glass synthesis may be Na2CO3, K2CO3, MgO, CaCO3, Al2O3, SiO2, or ZrO2. Here, the raw materials are added in a constant mixing ratio and then mixed while stirring using a mixer for 30 to 180 minutes.
[0089] In this step, it is more preferable to add Na2O at 12.5 to 13.5 mol% and K2O at 0.4 to 0.8 mol%. Here, it is most preferable to add the combined total of Na2O and K2O at 13 to 14 mol%.
[0090] In addition, at this stage, it is more preferable to add MgO and CaO in a combined amount of 1.5 to 2.5 mol%. Here, it is more preferable to add SiO2 and Al2O3 in a combined amount of 80 to 82 mol%.
[0091] In addition, at this stage, it is more preferable to add ZrO2 in an amount of 1.5 to 2.5 mol%. Here, it is most preferable to add at least one of B2O3 and P2O5 in an amount of 1.5 to 2.5 mol%.
[0093] melting
[0094] In the melting step (S120), the silicon dioxide-based glass composition is melted.
[0095] In this step, it is preferable to perform melting at 1,400 to 1,800°C for 1 to 6 hours, and more preferable to perform it at 1,500 to 1,700°C for 3 to 5 hours. If the melting temperature is below 1,400°C or the melting time is less than 1 hour, there is a problem that the components of the silicon dioxide-based glass composition are not completely melted, causing miscibility of the melted glass. Conversely, if the melting temperature exceeds 1,800°C or the melting time exceeds 6 hours, it is not economical because excessive energy and time are required.
[0097] annealing
[0098] In the annealing step (S130), the molten silicon dioxide-based glass composition is annealed and then cooled to form silicon dioxide-based oxide glass.
[0099] Here, it is preferable to perform cooling in a furnace. Since applying air or water cooling can cause severe internal stress in the glass and potentially lead to cracking, furnace cooling is preferred.
[0100] In this step, annealing is performed near the glass transition temperature. More specifically, it is preferable to perform annealing at 300 to 800°C for 30 to 360 minutes. If the annealing temperature is below 300°C or the annealing time is less than 30 minutes, the hardness of the glass may not be good. Conversely, if the annealing temperature exceeds 800°C or the annealing time exceeds 360 minutes, excessive energy consumption is required, making it uneconomical.
[0101] The silicon dioxide-based oxide glass produced by the above process is 7.5 × 10 -6 It has a coefficient of thermal expansion of / ℃ or less and a hardness of 800 Hv or more, more specifically, 6 × 10 -6 / ℃ to 7.5 × 10 -6 It has a coefficient of thermal expansion of / ℃ and a hardness of 800 to 900 Hv.
[0103] The method for manufacturing silicon dioxide-based oxide glass for vials having a hardness of 800 Hv or more according to the embodiment of the present invention described above produced silicon dioxide-based oxide glass having a low coefficient of thermal expansion and a high hardness of 800 Hv or more by strictly controlling each component of the glass composition and the ratio of the components thereof.
[0104] Thus, the method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention, by strictly controlling each component of the glass composition and the ratio thereof, 7.5 × 10 -6By having a low coefficient of thermal expansion of 1 / ℃ or less and a high hardness of 800 Hv or more, it is possible to manufacture a vial glass bottle that has excellent thermal stability and is resistant to external shock when used as a vial glass bottle.
[0105] As a result, the method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more according to an embodiment of the present invention is 7.5 × 10 -6 When silicon dioxide-based oxide glass that simultaneously satisfies a low coefficient of thermal expansion of 1 / ℃ or less and a high hardness of 800 Hv or more is used as a vial, the thermal stability of the vial can be secured, and the vial can be reliably protected from external shocks.
[0107] Examples
[0108] Hereinafter, the structure and operation of the present invention will be explained in more detail through preferred embodiments of the present invention. However, these are presented as preferred examples of the present invention and should not be interpreted in any way as limiting the present invention.
[0109] Details not listed here can be sufficiently technically inferred by a person skilled in this field, so their explanation will be omitted.
[0111] 1. Manufacture of silicon dioxide-based oxide glass
[0113] Examples 1 to 2
[0114] A silicon dioxide-based glass composition was prepared by mixing and stirring for 1 hour using a mixer with the composition and mixing ratio listed in Table 1.
[0115] Next, the silicon dioxide-based glass composition was melted at a temperature of 1,600°C for 4 hours.
[0116] Next, the molten silicon dioxide-based glass composition was cooled and then vitrified by annealing at 450°C for 120 minutes to produce a bulk silicon dioxide-based oxide glass. Here, the raw materials for Na2O, K2O, and CaO used in the manufacture of the oxide glass were Na2CO3, K2CO3, and CaCO3, respectively, and the remaining components were the same as those listed in Table 1.
[0118] Comparative Examples 1 to 4
[0119] A silicon dioxide-based glass composition was prepared by mixing and stirring for 1 hour using a mixer with the composition and mixing ratio listed in Table 1.
[0120] Next, the silicon dioxide-based glass composition was melted at a temperature of 1,600°C for 4 hours.
[0121] Next, the molten silicon dioxide-based glass composition was cooled and then vitrified by annealing at 450°C for 120 minutes to produce a bulk silicon dioxide-based oxide glass. Here, the raw materials for Na2O, K2O, and CaO used in the manufacture of the oxide glass were Na2CO3, K2CO3, and CaCO3, respectively, and the remaining components were the same as those listed in Table 1.
[0123] [Table 1] (Unit: mol%)
[0124]
[0126] 2. Evaluation of physical properties
[0127] Table 2 shows the results of measuring the coefficient of thermal expansion and hardness of silicon dioxide-based oxide glasses prepared according to Examples 1 and 2 and Comparative Examples 1 to 4. In addition, Figure 2 is a graph showing the results of measuring the coefficient of thermal expansion of silicon dioxide-based oxide glasses prepared according to Examples 1 and 2, and Figure 3 is a graph showing the results of measuring the Vickers hardness of silicon dioxide-based oxide glasses prepared according to Examples 1 and 2.
[0128] Here, the bulk silicon dioxide-based oxide glass prepared according to Examples 1 and 2 and Comparative Examples 1 to 4 was processed into a glass with dimensions of 5 (mm) × 5 (mm) × 25 (mm), and then the coefficient of thermal expansion was measured by TMA measurement. In addition, the bulk silicon dioxide-based oxide glass prepared according to Examples 1 and 2 and Comparative Examples 1 to 4 was processed into a glass with dimensions of 10 (mm) × 15 (mm) × 1 (mm), and then the hardness value was measured by hardness measurement using a Vickers hardness tester.
[0130] [Table 2]
[0131]
[0132] As shown in Tables 1 and 2 and Figures 2 and 3, the silicon dioxide-based oxide glass prepared according to Examples 1 and 2 has 7.5 × 10 -6 It was confirmed that it simultaneously satisfies a coefficient of thermal expansion of / ℃ or less and a hardness of 800 Hv or more.
[0133] On the other hand, the silicon dioxide-based oxide glass prepared according to Comparative Examples 1 to 4 is 7.5 × 10 -6 It was confirmed that it could not simultaneously satisfy a coefficient of thermal expansion of / ℃ or less and a hardness of 800 Hv or more.
[0134] As can be seen from the experimental results above, just like the silicon dioxide-based oxide glass prepared according to Examples 1 and 2, in addition to strictly controlling the component ratio of SiO2, at least one of B2O3 and P2O5 must be added to obtain 7.5 × 10 -6 It was confirmed that it has a low coefficient of thermal expansion of less than / ℃ and a high hardness of more than 800Hv.
[0136] Although the present invention has been described above with reference to embodiments, various changes and modifications can be made by those skilled in the art to which the present invention pertains. Such changes and modifications are considered to be within the scope of the present invention as long as they do not depart from the technical concept provided by the present invention. Accordingly, the scope of rights of the present invention should be determined by the claims set forth below. Explanation of the symbols
[0138] S110: Mixing step S120: Melting stage S130: Annealing step
Claims
Claim 1 A silicon dioxide-based oxide glass for a vial glass bottle comprising 12.5 ~ 13.5 mol% Na2O; 0.4 ~ 0.8 mol% K2O; 0.8 ~ 1.2 mol% MgO; 0.8 ~ 1.2 mol% CaO; 12 ~ 14 mol% Al2O3; 67 ~ 69.5 mol% SiO2; 1.5 ~ 2.5 mol% ZrO2; and 1 ~ 3 mol% of the sum of at least one of B2O3 and P2O5; wherein the silicon dioxide-based oxide glass is 6 × 10 -6 / ℃ to 7.5 × 10 -6 Silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more, characterized by having a coefficient of thermal expansion of / ℃ and a hardness of 800 to 900 Hv, and when the silicon dioxide-based oxide glass is used as a vial glass bottle, it ensures the thermal stability of the vial glass bottle while improving durability against external impact. Claim 2 delete Claim 3 Silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in claim 1, the sum of Na2O and K2O is 13 to 14 mol%. Claim 4 Silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in claim 1, the sum of the MgO and CaO is 1.5 to 2.5 mol%. Claim 5 Silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in claim 1, the sum of SiO2 and Al2O3 is 80 to 82 mol%. Claim 6 delete Claim 7 Silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in claim 1, the sum of one or more of B2O3 and P2O5 is 1.5 to 2.5 mol%. Claim 8 delete Claim 9 delete Claim 10 (a) a step of forming a silicon dioxide-based glass composition by mixing and stirring in a mixing ratio of 12.5 ~ 13.5 mol% Na2O, 0.4 ~ 0.8 mol% K2O, 0.8 ~ 1.2 mol% MgO, 0.8 ~ 1.2 mol% CaO, 12 ~ 14 mol% Al2O3, 67 ~ 69.5 mol% SiO2, 1.5 ~ 2.5 mol% ZrO2, and 1 ~ 3 mol% of the sum of at least one of B2O3 and P2O5; (b) a step of melting the silicon dioxide-based glass composition; and (c) a step of forming a silicon dioxide-based oxide glass by annealing the molten silicon dioxide-based glass composition and then cooling it; wherein, after step (c), the silicon dioxide-based oxide glass is 6 × 10 -6 / ℃ to 7.5 × 10 -6 A method for manufacturing silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more, characterized by having a coefficient of thermal expansion of / ℃ and a hardness of 800 to 900 Hv, and when the silicon dioxide-based oxide glass is used as a vial glass bottle, securing the thermal stability of the vial glass bottle while improving durability against external impact. Claim 11 delete Claim 12 A method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in claim 10, the above Na2O and K2O are in a combined total of 13 to 14 mol%. Claim 13 A method for manufacturing silicon dioxide-based oxide glass for a vial glass bottle having a hardness of 800 Hv or more, characterized in that, in step (a) above, the MgO and CaO are 1.5 to 2.5 mol% in total. Claim 14 A method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in step (a) above, the SiO2 and Al2O3 are 80 to 82 mol% in total. Claim 15 delete Claim 16 A method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in step (a) above, the sum of at least one of B2O3 and P2O5 is 1.5 to 2.5 mol%. Claim 17 A method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in step (b) above, the melting is carried out at 1,400 to 1,800°C for 1 to 6 hours. Claim 18 A method for manufacturing silicon dioxide-based oxide glass for vial glass bottles having a hardness of 800 Hv or more, characterized in that, in step (c) above, the annealing is performed at 300 to 800°C for 30 to 360 minutes. Claim 19 delete Claim 20 delete
Citation Information
Patent Citations
Composition for preparing aluminosilicate glass, aluminosilicate glass as well as preparation method and application of aluminosilicate glass
CN114988698A
Glasses having improved toughness and scratch resistance
KR1020100091228A
Durable glass housings / enclosures for electronic devices
KR1020110050522A
Tempered glass plate, method for manufacturing tempered glass plate, and tempered glass plate
KR1020250002137A
Glass for pharmaceutical container and glass tube for pharmaceutical container
JP2017218353A
